2018
DOI: 10.1111/all.13461
|View full text |Cite
|
Sign up to set email alerts
|

Neonates colonized with pathogenic bacteria in the airways have a low‐grade systemic inflammation

Abstract: The composition of the upper airway microbiome in early life may cause systemic low-grade inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Despite the fact that respiratory IAV infection went unchanged, we explored whether respiratory carriage with B. bronchiseptica affected responses against a systemic bacterial infection. Of note, only recently asymptomatic colonization with Moraxella catharralis , Haemophilus influenzae, and/or Streptococcus pneumoniae in the hypopharynx, was shown to be associated with low-grade systemic inflammation in new-born children [ 18 ]. Surprisingly, we found B. bronchiseptica carriage to display a significant benefit for the host, regarding the control of systemic L. monocytogenes infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that respiratory IAV infection went unchanged, we explored whether respiratory carriage with B. bronchiseptica affected responses against a systemic bacterial infection. Of note, only recently asymptomatic colonization with Moraxella catharralis , Haemophilus influenzae, and/or Streptococcus pneumoniae in the hypopharynx, was shown to be associated with low-grade systemic inflammation in new-born children [ 18 ]. Surprisingly, we found B. bronchiseptica carriage to display a significant benefit for the host, regarding the control of systemic L. monocytogenes infection.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is an increasing awareness of immune regulatory effects across compartments to remote sites, which to date are most appreciated for the gut microbiome [ 13 , 15 , 16 ]. Nevertheless, there is also evidence for inflammatory processes in the respiratory tract to influence systemic immunity [ 13 , 17 , 18 , 19 ]. While we are only beginning to understand these multi-faceted interactions, the underlying mechanisms to date remain mostly elusive.…”
Section: Introductionmentioning
confidence: 99%
“…St. aureus was associated with a TH17 profile and elevated IL-17; of note, there was no signal with S. pneumoniae colonization. Subsequent work on outcomes in colonized children has shown that they have increased troublesome non-specific respiratory symptoms (74), an increased risk of bronchiolitis and pneumonia (75), and interestingly, have low grade systemic inflammation as shown by an elevated hs-CRP (76). Furthermore, children given a diagnosis of asthma at age 7 years were shown to have increased levels of IL-5 and IL-13 when their peripheral blood mononuclear cells harvested at age 6 months were stimulated with H. influenzae, M. catarrhalis , and S. pneumoniae , and also increased IL-17 and IL-10 when stimulated by H. influenzae and M. catarrhalis , but not S. pneumoniae (72, 73).…”
Section: The First Steps: Episodic Viral Wheezementioning
confidence: 99%
“…Additionally, the immune system might also affect the risk of bacterial airway colonization with microorganisms 26 . Airway bacterial carriage in early life has been associated with a low‐grade systemic inflammation at age 6 months, including C‐reactive protein and interleukin‐6, which could also affect the risk of wheezing or asthma 27 . Bacterial carriage might influence the risk of lower respiratory tract infections and vice versa 21 .…”
Section: Discussionmentioning
confidence: 99%